The development of board game activities to enhance Executive Function (EF) skills in elementary school children - Fak-on, Pachatchaya; Promsonthi, Wijitta (Mahachula Academic Journal, 2026)
The development of board game activities to enhance Executive Function (EF) skills in elementary school children had the following objectives: To develop a set of board game activities to enhance EF skills in elementary school children with an efficiency criterion of 80/80. To study the effects of using these board game activities on the EF skills of elementary school children. The research sample consisted of 170 students from grades 4-6 studying in schools under the Educational Fund Project in Phra Nakhon Si Ayutthaya Province. The sample was selected through simple random sampling. Research instruments included: A structured interview form for classroom teachers on cognitive skills, consisting of 10 items. An EF skills assessment for elementary students in three areas: Working Memory, Response Inhibition, and Flexibility. This assessment used a 5-point Likert scale and consisted of 15 items. Data analysis employed E1/E2 efficiency analysis and dependent t-test to analyze the differences in development before and after the activities. Research findings: The board game activities to enhance EF skills in elementary school children achieved an efficiency of 80.89/81.73. Elementary school children’s EF skills scores after participating in the board game activities were significantly different from their scores before the activities at the .05 level of statistical significance. When considering the mean scores, it was found that after participating in the board game activities to enhance EF skills, elementary school children had higher average scores than before the activities.